5(3x+12)-12x=

Simple and best practice solution for 5(3x+12)-12x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(3x+12)-12x= equation:


Simplifying
5(3x + 12) + -12x = 0

Reorder the terms:
5(12 + 3x) + -12x = 0
(12 * 5 + 3x * 5) + -12x = 0
(60 + 15x) + -12x = 0

Combine like terms: 15x + -12x = 3x
60 + 3x = 0

Solving
60 + 3x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-60' to each side of the equation.
60 + -60 + 3x = 0 + -60

Combine like terms: 60 + -60 = 0
0 + 3x = 0 + -60
3x = 0 + -60

Combine like terms: 0 + -60 = -60
3x = -60

Divide each side by '3'.
x = -20

Simplifying
x = -20

See similar equations:

| 5.5x+19=6.75x+9 | | 30-x=2x+3 | | 30x=12 | | 16+8x=x^2 | | t+68=7t-58 | | 4x-5+2(x-3)=12x+5 | | 6-4y=14 | | 7x-25=-63 | | 3p-28=180 | | 1+1.5ln(x+1)=10 | | 8(9+8x)+12= | | 4(2y-5)-12y= | | 13=8x-4 | | -5(x+5)=-9x-17 | | -5w-6=19 | | 2-5/2p=53/4 | | (2/3)y-15=180-(36-3(90-2/3y-15)) | | 16x^2-9x+1=0 | | 3(4+5m)=102 | | -2(y+6)-(y+3)= | | a(a+3)+a(a-6)+35=a^2+7 | | 80x=40x | | 16-5(3-1)=22 | | 4floz=tsp | | 8cm=2.5 | | 8x-13=-19 | | -3x+5x+4x=-5 | | -42-37=-79 | | 1.23x=8.856 | | 12x-25=-20 | | D+8=25 | | -2(w+3)+5w= |

Equations solver categories